2021
DOI: 10.3389/fonc.2021.793006
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Membranes Coated Gold Nanocages for Tumor Targeted Drug Delivery and Amplificated Low-Dose Radiotherapy

Abstract: Continuous high doses of radiation can cause irreversible side effects and radiation resistance; thus, advanced radiosensitizers are urgently needed. To overcome this problem, we developed a nano platelet radiosensitization system (PCA) by coating the chemotherapeutic drug cisplatin (CDDP) loaded gold nanocages (AuNs) within the platelet membrane. The developed PCA system may enable AuNs to have immune escape and targeting capabilities. After administration, PCA will actively target tumor cells and avoid being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Cellular uptake is an important basis for nanodelivery drugs. Studies have revealed that platelet membranes potentiate drug-carrying particles the ability to be taken up by tumors and to target tumor cells [ 19 , 20 ]. We further investigated the interactivity between PLTM - coated nanoparticles and hepatocellular carcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular uptake is an important basis for nanodelivery drugs. Studies have revealed that platelet membranes potentiate drug-carrying particles the ability to be taken up by tumors and to target tumor cells [ 19 , 20 ]. We further investigated the interactivity between PLTM - coated nanoparticles and hepatocellular carcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…This is very important. Although many nanomaterials have good killing effect on tumors, they also have corresponding physiological toxicity, which limits their long-term biological and clinical value [36]. The treatment schedule is shown in Figure 5(c).…”
Section: Colony Formation Assay Also Demonstrated Consistent Results ...mentioning
confidence: 99%
“…Therefore, the RT sensitizer based on platelet membrane was developed to achieve enhanced RT results. 54 Leukocytes Membrane. Immune cells are leukocytes, which play a vital role as "patrol soldiers" in the human immune system.…”
Section: ■ Cells Membrane Coatingmentioning
confidence: 99%
“…PCA with the capacity of targeting and radiosensitization enables nanodrugs to overcome renal effects and escape immune elimination. Therefore, the RT sensitizer based on platelet membrane was developed to achieve enhanced RT results …”
Section: Cells Membrane Coatingmentioning
confidence: 99%